Pesticide poisoning in Aotearoa New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Torrington, Ciaran Dawn (Massey University, 2015)
As a nation for over 70 years New Zealand has used unprecedented amounts of pesticides within our workplaces, homes, lands, communities and our National Parks. The health and environmental hazards from exposure to pesticides is now well accepted within Science, but as an illness pesticide poisoning is not well acknowledged within society. Historically pesticide poisoning has been strongly contested by Science, Government, Medicine, Business & Industry and as a result people who have experienced illness from pesticide poisoning frequently encountered denial or de-legitimisation of their illness stories. Despite the long history of pesticide use in this country no study has considered what it is like to experience pesticide poisoning in workplaces in New Zealand, and this study attempts to redress this lack of research effort. A narrative methodology and theories was employed because it explores an illness experience in depth, allows for marginalised stories such as pesticide poisoning to be explored, and is a popular method for exploring health experiences within the Social Sciences. There were sixteen participants interviewed who had experienced pesticide poisoning in their workplaces in New Zealand. This thesis presents three perspectives of narrative theory of the pesticide poisoning experience. The first perspective is of the overarching narrative of pesticide poisoning in New Zealand which shows how the narratives of this study are distinctly automythology quest narratives. The second perspective is how the narratives are structured to give form and meaning, and within this study the narratives are structured within the domains of the Whare Tapa Wha conceptual model of health and the study demonstrates how this can form a foundation for an embodied perspective of health and identity. The third perspective considers the social forces that surround and influence pesticide poisoning illness stories. The participants reconstruct their sense of identity in response to the illness experience and actively advocate for change within their environment. The narratives of this study are surrounded by the powerful authority over knowledge by powerful institutions who sought to deny their experiences of pesticide poisoning.
Keywords: Pesticides; Health aspects; Industrial toxicology; Psychological aspects; New Zealand; Poisoning; Contested illness; Narrative; Automythology; Whare tapa wha; Embodied; Authority; Aotearoa